Access to Maternal Health Services During the COVID-19 Pandemic: Experiences of Indigent Mothers and Health Care Providers in Kilifi County, Kenya - Ombere, Stephen Okumu (Frontiers in Sociology, 2021)
COVID-19 has spread rapidly in Kenya and has not spared pregnant women. Evidence from Kenya shows that during the COVID-19 pandemic, health systems have been either stressed to their maximum capacity or are becoming overwhelmed. However, the population is advised not to attend hospital unless strictly necessary, and this advice seems to apply to all, including expectant mothers. There is a dearth of information on how poor expectant mothers with low bargaining power cope during COVID-19 in Kenya, which this study addresses for those in Kilifi County. This rapid qualitative study draws data from an extensive literature review and from interviews with 12 purposively selected mothers who were either expectant or had newborn babies during the pandemic in Kilifi County. Five matrons-in-charge of maternal health services and four traditional birth attendants were also interviewed via mobile phone. Data were analyzed thematically and are presented in a textual description. It emerged that expectant mothers feared attending hospitals for perinatal care due to the possibility of contracting COVID-19. Therefore, there was an increase in home deliveries with the assistance of traditional birth attendants (TBAs)/traditional midwives, who were also overwhelmed with women who sought their services. Since most causes of maternal morbidity and mortality can be prevented by prompt, suitable treatment by qualified health practitioners, the health officials interviewed recommended training and integration of TBAs in emergency healthcare responses to help during crises in MHS because they are trusted by their local communities. Notably, such integration of traditional midwives should be supported and should also include additional training and monetary incentives.